2011
DOI: 10.1007/s15010-011-0190-9
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of prior long-term versus short-term statin use on the mortality of bacteraemic patients

Abstract: Statins reduce the 30-day in-hospital all-cause mortality of bacteraemic patients. Long-term statin use prior to the bacteraemia improves the survival of bacteraemic patients more than short-term statin use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 34 publications
(32 reference statements)
4
30
1
5
Order By: Relevance
“…These reviews included studies on infections such as bacteremia, pneumonia, sepsis, and some acute infections, and the patient populations received several different statins. For instance, two single-center retrospective studies showed that patients with bacteremia who had undergone prior statin treatment have significantly decreased risks of in-hospital mortality of 6% versus 28% (P ϭ 0.002) and 13% versus 24% (P ϭ 0.001), respectively (14,15). The latter study also showed that there was an inverse correlation between the duration of statin treatment and the risk of mortality in comparisons of statin use Ն12 and Ͻ12 weeks prior to infection (11% versus 14%, P ϭ 0.04) (15).…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 99%
See 1 more Smart Citation
“…These reviews included studies on infections such as bacteremia, pneumonia, sepsis, and some acute infections, and the patient populations received several different statins. For instance, two single-center retrospective studies showed that patients with bacteremia who had undergone prior statin treatment have significantly decreased risks of in-hospital mortality of 6% versus 28% (P ϭ 0.002) and 13% versus 24% (P ϭ 0.001), respectively (14,15). The latter study also showed that there was an inverse correlation between the duration of statin treatment and the risk of mortality in comparisons of statin use Ն12 and Ͻ12 weeks prior to infection (11% versus 14%, P ϭ 0.04) (15).…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 99%
“…For instance, two single-center retrospective studies showed that patients with bacteremia who had undergone prior statin treatment have significantly decreased risks of in-hospital mortality of 6% versus 28% (P ϭ 0.002) and 13% versus 24% (P ϭ 0.001), respectively (14,15). The latter study also showed that there was an inverse correlation between the duration of statin treatment and the risk of mortality in comparisons of statin use Ն12 and Ͻ12 weeks prior to infection (11% versus 14%, P ϭ 0.04) (15). A meta-analysis of available published data found that the use of statins was specifically associated with a reduced risk of morbidity and mortality resulting from pneumonia (12).…”
Section: Clinical Evidence That Statins Influence Morbidity and Mortamentioning
confidence: 99%
“…Alguns estudos descrevem prováveis efeitos positivos da terapia com estatinas no quadro inflamatório da sepse [27][28][29][30][31] . O efeito das estatinas na progressão da sepse com administração imediata e contínua somente após a internação foi investigado em dois estudos 27,30 , nos quais foram selecionados pacientes sép-ticos para receber o medicamento durante o período de internação e seus efeitos foram comparados ao do grupo placebo.…”
Section: Resultsunclassified
“…Desta forma, a relevância da redução dos níveis de citocinas exercendo um efeito protetor na sepse e apresentando um possível benefício clínico ainda permanece inconclusivo. Esses ensaios clínicos controlados se basearam em evidências advindas de estudos retrospectivos e prospectivos observacionais anteriores, demonstrando que pacientes em tratamento com estatina pré e pós-hospitalização tiveram melhores resultados nas taxas de progressão da sepse e sobrevida quando comparados a outros grupos 29,31 . Donnino et al 31 , em estudo retrospectivo, investigaram a associação entre a terapia com estatinas e a taxa de mortalidade em pacientes internados com suspeita de infecção.…”
Section: Resultsunclassified
See 1 more Smart Citation